Effect of Fibrolytic Microbes and Enzymes on Biochemical Blood Parameters in Crossbred Calves - Kapadiya, RI; Shah, SV; Patel, YG; Pandya, PR (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Twenty crossbred (HF x Kankrej) calves were allotted randomly to five groups (each had one male and three female calves) almost with similar body weight (85.70 ± 6.37 kg) and age (167.55 ± 21.70 days). Experimental calves of the control group were offered hybrid napier untreated, and the other four groups were offered hybrid napier treated with (i) fungus- Aspergillus spp. (1×107 per g feed), (ii) fibrolytic bacteria- Escherichia spp. (106 CFU per g feed), (iii) xylanase (50 mL/kg having xylanase 1.2 IU/mL), and (iv) consortium of 1/3rd dose of fungus + bacteria + enzyme as treatments for 140 days. The blood samples were collected from each calf at a biweekly intervals in the EDTA vacuttee. Nutrients offered to crossbred calves were sufficient to satisfy the nutrients requirements. Bacteria fed calves had significantly higher (p <0.05) mean hemoglobin levels than control. Blood plasma glucose of calves in fibrolytic microbes and enzyme groups was statistically similar to control. Feeding of fungus, bacteria, enzyme, and consortium was without a significant effect on plasma total proteins. In comparison to control (7.53 mg/dL), the plasma phosphorus was significantly (p <0.05) higher in calves fed enzyme (7.87 ± 0.20 mg/dL) and lower in group fed fungus (7.13 mg/dL). In contrast, in bacteria (7.57 mg/dL) and consortium group (7.60 mg/dL) it was statistically similar to control. Plasma glutamic pyruvic transaminase concentration of crossbred calves was lower (p <0.05) in enzyme and higher (p <0.05) in fungus, bacteria, and consortium groups than in control, while plasma glutamic oxaloacetate transaminase concentration in all groups was statistically similar. In conclusion, all blood parameters of different groups were within normal range and without adverse effect on the overall performance of calves.